Sistem Pakar Deteksi Dini Gejala Poliycystic Kidney Disease (PKD) Menggunakan Metode Forward Chaining Berbasis Android - Aldisa, Rima Tamara (KITA Institut, 2022)
The purpose of this study is to build an application with the forward chaining method used to diagnose Polycystic Kidney Disease based on Android. The research method consists of analysis and design, while the use case diagram is used as a model of the system to be built, Forward Chaining is implemented in the system to diagnose Polycystic Kidney Disease and the application is built based on Android. The conclusion from the results of this study is to show the application features that are made to run. An expert system application designed to be able to help Polycystic Kidney Disease based on the symptoms entered by the user using the Forward Chaining method.